Sex-Dependent Dyslipidemia and Neuro-Humoral Alterations Leading to Further Cardiovascular Risk in Juvenile Obesity - Simoes, Estefania; Correia-Lima, Joanna; Calfat, Elie Leal de Barros; Otani, Thais Zélia dos Santos; Vasques, Daniel Augusto Correa; Otani, Victor Henrique Oyamada; Bertolazzi, Pamela; Kochi, Cristiane; Seelaender, Marilia; Uchida, Ricardo Riyoiti (Frontiers in Nutrition, 2021)
Objective: Childhood obesity is a growing concern as the World Health Organization (WHO) estimates that over 38 million children under the age of 5 are overweight or with obesity. This condition is the reflex of energy imbalance between the calories consumed and those expended. Sex-related responses associated with dyslipidemia, hormonal alterations and neurohumoral disruptions in childhood obesity are the focus of the present investigation. Methods: Data from ninety-two Brazilian adolescents were enrolled and divided between obesity and eutrophic group. Obesity was classified using body mass index Z- score according age and weight. Anthropometrical analyses, blood pressure, blood lipids, metabolism-regulating hormones and neuropeptides were carried out. Results: Systolic blood pressure was higher in females and males with obesity. Females with obesity presented alterations in lipid profile and an augment of cardiovascular diseases prediction ratios TC/HDL, TG/HDL, LDL/HDL and VLDL/HDL. The leptin, GIP and neuropeptide levels showed sex-dimorphism dependence in obesity. Children with obesity presented increased levels of circulating insulin, c-peptide, amylin, glucagon and GLP-1. Correlation analysis showed significant linearity between body mass index, blood pressure, lipids, lipoproteins, hormones and neuropeptides content. Conclusions: Our data support an existing link between hypertension, dyslipidemia and neuro-hormonal imbalance in childhood obesity. We also described a sex-dependent pattern in childhood obesity-associated dyslipidemia and blood pressure in females with obesity, solely.